Geospeciation of arsenic using MINTEQA2 for a post-mining lake - Sari, Seri Adelila; Ujang, Zaini; Ahmad, Umi Kalthom (2006)
The objective of this study was to investigate the cycling of arsenic in the water column of a post-mining lake. This study is part of the research project to develop health risk assessment for the surrounding populations. Inductively Coupled Plasma-Mass Spectrophotometer (ICP-MS) and Capillary Electrophoresis (CE) techniques have been used to analyze the total amount and speciation of arsenic. A computer program, called MINTEQA2, developed by United States Environmental Protection Agency (USEPA) was used for predicting the arsenic, iron, and manganese as functions of pH and solubility. The pH values and cycle of arsenic showed that the percentage of bound arsenate, As (V) species in form of HAsO4- increased with pH range from 5 to 7, as well as Fe (II) and Mn (II). As expected, phases of arsenic oxides are FeAsO4 and Mn3(AsO4), as a function of solubility, were found not to be over saturated and not precipitated. This indicated that the phases of arsenic oxides have a high solubility.